Performance Evaluation of VoIP Service for Emergency Disaster Responses over WiMAX-WLAN Integrated Network - Prasetiyono Hari Mukti; Syaldi Kharisma Ananda; Gatot Kusrahardjo (JURNAL NASIONAL TEKNIK ELEKTRO, 2022)
As a very large archipelago country, Indonesia has a high intensity of the natural disaster. In many cases, the telecommunication infrastructure collapse during the disaster. Therefore, a prominent and robust emergency telecommunication network is required. In this paper, an implementation of VoIP services over the WiMAX-WLAN integrated network is proposed. The integrated network is designed to provide an alternative of the emergency network during the disaster response. The VoIP service is selected for the study case because this service can be used as a complementary of the telephony service. In this paper, the WiMAX network is designed based on the IEEE Standard 802.16-2004 with the frequency band of 3.5 GHz while the WLAN network is designed based on the IEEE Standard 802.11n. To support many scenarios of network topology, the proposed integrated network is designed in P2P and PMP topologies. Within these network topologies, the network performance is evaluated in terms of delay, jitter, throughput and packet loss, as well as MOS value. The network performance is evaluated over various background traffic. From the experimental evaluation, it shows that the network becomes worse when the network load that is represented by the background traffic exceeding 3 Mbps. In general, there is no significant performance different between P2P and PMP network topology.